'But I Know You, You Are Not God': African Responses to European Colonialism in a Missionary Newspaper. Issue 4 (15th August 2020) - Volz, Stephen
Abstract : This article analyses how African letter-writers in the missionary-edited Setswana newspaper Mahoko a Becwana (1883–96) sought to make sense of expanding European power during the 'scramble for Africa' and its accompanying social and political changes. The newspaper wrestled with readers' opinions on a wide range of contentious topics, including ethnic identity, literacy, chieftaincy, colonial government, alcohol, adolescent initiation, marriage, religion and rational thought in general. The article questions the prevalent emphasis on European hegemony and highlights ways in which Africans managed to develop and maintain a separate discourse beyond European control or description as they critiqued and selectively adopted various elements of European culture. During the late 19th century, most Setswana-speaking people still regarded their populous chiefly capitals as the centres of society and relatively new European towns as peripheral, and they expected to maintain their autonomy while adapting to new circumstances. Those expectations would soon be severely challenged by rinderpest, war, industrialisation and the entrenchment of European power, but, building on their previous strategies, they initially pursued ways to accommodate European colonisation that preserved their existing communal strength.